Voluntary and involuntary lending: A test of major hypotheses - Peter Nunnenkamp (World Bank, Policy, Planning, and Research Complex, 1989)
This paper assesses the empirical relevance of various conjectures about what determined whether creditors would issue loans to developing countries in the 1980s. With the onset of the debt crisis, private creditors began to honour debtors who improved economic performance and policies. Private creditors were not prepared to compensate for unfavourable developments in the world market with additional lending. Small borrowers who did not benefit from involuntary lending had great difficulty attracting further capital inflows when they were hit by external shocks. The paper finds that if debtors are given more incentive to meet debt obligations through more efficient economic policies, creditors will be more likely to share the credit risks triggered by unfavourable developments in the world market. As the distribution of credit risks between debtors and creditors improves, the capital outflow from developing countries will be checked.
Keywords: 330